2021
DOI: 10.1039/d0py01754j
|View full text |Cite
|
Sign up to set email alerts
|

RAFT polymerisation of trifluoroethylene: the importance of understanding reverse additions

Abstract: This article is the first report of the RAFT polymerisation of trifluoroethylene (TrFE). Trifluoroethylene is a rare but very important fluoromonomer, as it allows the preparation of materials endowed with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…A study of the TrFE RAFT polymerisation mechanism will be reported elsewhere. 22 The complete assignments of the chain-end signals for the PTrFE product made by RAFT was made possible by a set of 1D and 2D 1 H, 19 F and 13 C NMR experiments.…”
Section: Resultsmentioning
confidence: 99%
“…A study of the TrFE RAFT polymerisation mechanism will be reported elsewhere. 22 The complete assignments of the chain-end signals for the PTrFE product made by RAFT was made possible by a set of 1D and 2D 1 H, 19 F and 13 C NMR experiments.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the RAFT polymerization of trifluoroethylene in the presence of xanthate was also successfully achieved with controlled molar masses and dispersities. 34 4.1.3. Synthesis via Organometallic-Mediated Radical Polymerization (OMRP).…”
Section: Synthesis Via Reversible Deactivation Radical Polymerization...mentioning
confidence: 99%
“…More recently, the RAFT polymerization of trifluoroethylene in the presence of xanthate was also successfully achieved with controlled molar masses and dispersities …”
Section: Sequence Regulation In Synthetic Fluoropolymersmentioning
confidence: 99%
“…The SI-RAFT approach is of particular interest for the fluoropolymers as recent work showed that VDF as well as TrFE polymerisation could be controlled using xanthate agents. [44][45][46][47] Indeed, even if those monomers are prone to backwards additions, the RAFT polymerisation using O-Ethyl-S-(1methoxycarbonyl) ethyldithiocarbonate could afford an acceptable degree of control. In the present study, piezoelectric composites integrating barium titanate (BTO) nanoparticles incorporated into a P(VDFco-TrFE) copolymer matrix were prepared and their piezoelectric properties investigated.…”
Section: Introductionmentioning
confidence: 99%